FRÚGOLI JR., Heitor; ANDRADE, Luciana Teixeira & PEIXOTO, Fernanda Arêas (orgs.). A cidade e seus agentes: práticas e representações, Belo Horizonte/São Paulo, PUC Minas/EDUSP, 2006, 408 pp. - Machado, Giancarlo Marques Carraro (Revista de Antropologia, 2013)
FRÚGOLI JR., Heitor; ANDRADE, Luciana Teixeira & PEIXOTO, Fernanda Arêas (orgs.). A cidade e seus agentes: práticas e representações, Belo Horizonte/São Paulo, PUC Minas/EDUSP, 2006, 408 pp.